The Performance of the Dikyasa Unit through the Traffic Dikmas in Reducing Traffic Violations in the Legal Area of the Parigi Moutong Police - Komang Sri Ayu Kumala (Police Studies Review, 2021)
The focus of this thesis research is on the performance of the Dikyasa Unit through the Traffic Dikmas in reducing traffic violations in the jurisdiction of the Parigi Moutong Police. The focus of this study is considered important because the performance, quality, quantity, implementation of duties and responsibilities of the Dikyasa Unit personnel are role models for implementing field activities in reducing traffic violations in the community. There are three issues raised in this thesis research, namely: (1) What is the general description of traffic violations in the jurisdiction of the Parigi Moutong Police? (2) How is the performance of the Dikyasa Unit through the local community education unit in reducing traffic violations in the jurisdiction of the Parigi Moutong Police? (3) What are the factors that affect the performance of the Dikyasa Unit through the local community education unit in reducing traffic violations in the jurisdiction of the Parigi Moutong Police? Using a conceptual framework in the form of theories and concepts used as an analytical knife by the author in answering the predetermined problem formulation. Theories and concepts used by the author are performance theory, SWOT theory, the concept of social education and security, the concept of traffic safety and security, and the concept of traffic violations. The findings in this study are (1) Traffic violations occur due to lack of awareness in the community and the influence of local cultural factors, (2) Dikyasa Unit performance is less than optimal in quality, quantity, implementation of duties and responsibilities when implementing community education activities in the field. , (3) the less than optimal performance of the engineering unit is caused by internal factors and external factors so that the competencies possessed by the engineering unit need to be improved.